Kualitas Produk dan Kualitas Layanan terhadap Keputusan Pembelian yang Dimediasi oleh Citra Merek pada Penjualan Kendaraan Bermotor Roda Empat - Tonibun Tonibun; Saparso Saparso; Soegeng Wahyoedi (Journal of Management and Bussines (JOMB), 2021)
This study aimed to determine the effect of product quality and service quality on purchasing decisions mediated by brand image on the sale of Wuling four-wheeled motorized vehicles. This research was conducted by non-probability sampling method with purposive sampling type. Data analysis using Smart PLS 3.3. The results showed, the value of p values ​​sequentially on the influence of brand image on purchasing decisions, service quality on brand image, service quality on purchasing decisions, product quality on brand image, product quality on purchasing decisions, product quality on purchasing decisions mediated by image. Brands, Service Quality on Purchase Decisions Mediated by Brand Image are 0.311, 0.000, 0.000, 0.000, 0.133, 0.343, 0.000. In conclusion, service quality, product quality have a significant effect on brand image, and service quality has a significant effect on purchasing decisions mediated by brand image. Meanwhile, brand image, product quality has no significant effect on purchasing decisions, and product quality has no significant effect on purchasing decisions mediated by brand image. Keywords: Product Quality, Service Quality, Brand Image, Purchase Decision